Efficacy of Prednisolone in Generated Myotubes Derived From Fibroblasts of Duchenne Muscular Dystrophy Patients - Kameyama, Tsubasa; Ohuchi, Kazuki; Funato, Michinori; Ando, Shiori; Inagaki, Satoshi; Sato, Arisu; Seki, Junko; Kawase, Chizuru; Tsuruma, Kazuhiro; Nishino, Ichizo; Nakamura, Shinsuke; Shimazawa, Masamitsu; et al. (Frontiers in Pharmacology, 2018)
Abstract Duchenne muscular dystrophy (DMD) is a recessive X-linked form of muscular dystrophy characterized by progressive muscle degeneration. This disease is caused by the mutation or deletion of the dystrophin gene. Currently, there are no effective treatments and glucocorticoid administration is a standard care for DMD. However, the mechanism underlying prednisolone effects, which leads to increased walking, as well as decreased muscle wastage, is poorly understood. Our purpose in this study is to investigate the mechanisms of the efficacy of prednisolone for this disease. We converted fibroblasts of normal human cell line and a DMD patient sample to myotubes by MyoD transduction using a retroviral vector. In myotubes from the MyoD-transduced fibroblasts of the DMD patient, the myotube area was decreased and its apoptosis was increased. Furthermore, we confirmed that prednisolone could rescue these pathologies. Prednisolone increased the expression of not utrophin but laminin by down-regulation of MMP-2 mRNA. These results suggest that the up-regulation of laminin may be one of the mechanisms of the efficacy of prednisolone for DMD.